Emotional states, achievement goals, and performance in NCAA Division I swimmers - Wilt, J. A.; Johnson, S. E. (Scientific Journal of Sport and Performance, 2023)
There is much interest in how emotions and achievement goals predict sports performance, yet little research has examined these topics in elite swimmers. This study involving NCAA Division 1 swimmers aimed to (a) present descriptive information on emotions and goals related to training and meets and (b) predict performance from emotions and 2 x 2 (performance-mastery x approach-avoidance) achievement goals. Over the course of five meets, 13 swimmers (4 men, 9 women) completed weekly ratings of bipolar emotional dimensions (e.g., sluggish-energetic) and achievement goals regarding their training. One day prior to meets, swimmers rated the same emotions and goals regarding the upcoming meet. Event performance was recorded in standardized FINA points. Swimmers (a) experienced neutral emotions (close to the midpoint of bipolar scales) regarding training and positive emotions about meets and (b) endorsed high levels of approach goals and moderate levels of avoidance goals. Correlational analyses revealed that positive emotions associated positively with approach goals and negatively with mastery-avoidance goals. Multilevel models predicting performance from emotions and goals showed sparse associations, with some evidence indicating that increases in energy and decreases in performance avoidance goals prior to a meet related to better performance. We discuss the implications of these findings.